China's Long-Term Low-Carbon Development Strategies and Pathways Comprehensive Report - Institute of Climate Change and Sustainable Development of Tsinghua University et al (Springer Nature Singapore : Imprint: Springer, 2022)
This open access book introduces a multi-disciplinary and comprehensive research on China's long-term low-carbon emission strategies and pathways. After comprehensively considering China's own socioeconomic conditions, policy design, energy mix, and other macro-development trends and needs, the research team has proposed suggestions on China's low-carbon development strategies and pathways until 2050, with required technologies and policies in order to realize the goals of building a great modern socialist country and a beautiful China. These achievements are in conjunction with the climate goals set in the Paris Agreement alongside Global Sustainable Development. The authors hope that the research findings can serve as a reference for all sectors of Chinese society in their climate research efforts, offer support for the formulation and implementation of china's national low-carbon development strategies and policies, and help the world to better understand China's story in the general trend of global green and low-carbon development.